(untitled) (Revista de Ciências Agroveterinárias, 2020)
Recent studies have shown that the main origin factor of the retractable character observed in Latossolos and Nitossolos is not mineralogy. Thus, it was hypothesized that soil shrinkage in Latossolos and Nitossolos originates from soil structural factors, so they can be investigated indirectly through the physical properties of soil structure. Thus, the objective of this work was to relate the shrinkage with physical properties and the organic matter of the soil, indirectly investigating the process of soil shrinkage. Six profiles collected in the states of Santa Catarina and Rio Grande do Sul were selected, which have a retractable character and one Vertissolo Ebânico in Rio Grande do Sul. The following were evaluated: particle size, consistency limits, soil and particle density, total porosity, micropores. and macropores, specific surface area, shrinkage index, soil organic matter and soil water retention. The relationship between the properties was performed through principal component analysis (PCA). Additionally, to analyze the effect of structure and organic matter on shrinkage index, samples were collected on the A, AB, BA, Bt1, Bt2, Bt3 horizons of the Nitossolo Bruno of Painel, which has a natural gradient of matter decrease organic in profile. In this, the retention curve and shrinkage index determinations were performed with preserved and altered structure samples. The PCA indicated the plasticity index most closely related to soil shrinkage, indicating that the reduction in water content creates menisci between the particles so the surface tension increases causing a meniscus curvature at the interface between water and air bringing the particles closer together, thus causing soil shrinkage. Organic matter has a direct effect on the shrinkage process; however, the shrinkage intensity is dependent on soil structure.